Ammoniacal nitrogen removal via dendrocalamus asper biochar-activated carbon - Wan Hamid, Sharifah Nadzirah; Samsudin, Nur Shafiqah; Abdul Karim, Siti Kartina; Idris, Juferi (Universiti Teknologi MARA, Sarawak, 2025)
The porous architecture and series of surface functional groups of bamboo-derived biochar have demonstrated promising potential for flocculation and coagulation in wastewater treatment applications. Dendrocalamus asper biochar (pyrolysed at 900 °C in N2 for 5 hours) was subjected to additional carbonisation and chemically activated with KOH (5:1 w/w) in a furnace at 500 °C for 2 hours to produce activated carbon. The objectives were to determine the optimal mass dosage for ammoniacal nitrogen removal, quantify the adsorption capacity (Qₑ, mg g-1), and characterise surface functional groups via Fourier-transform infrared spectroscopy (FTIR). FTIR spectra of treated and untreated biochar revealed O–H stretching, aromatic rings, and C=C alkenes, indicating similar functional profiles. KOH-treated biochar achieved a maximum adsorption capacity of 46.08 mg g-1 versus 44.11 mg g-1 for untreated biochar at an optimal contact time of 143 minutes. Increasing biochar dosage marginally decreased qₑ due to competitive adsorption–desorption phenomena, yet enhanced removal efficiency. The treated biochar exhibited only marginal improvements, achieving a 2.85% increase in removal efficiency and a 1.97 mg g-1 increase in adsorption capacity. Kinetic analysis confirmed that ammoniacal nitrogen adsorption adhered to a pseudo-second-order model (r² = 0.9933–1.000), with rate constants (k₂) ranging from 1.827 × 10⁷ to 6.5828 × 10⁶ h⁻¹ and modelled qₑ between 55.49 and 59.41 mg g-1. The results demonstrate that both treated and untreated bamboo biochars are effective in removing ammoniacal nitrogen with negligible performance disparity. It is suggested to optimise activation parameters, including duration, temperature, and impregnation ratio. Additionally, conducting proximate or ultimate analysis, measuring the BET surface area, and performing SEM characterisation are recommended for a comprehensive evaluation.